Opting for oil the political economy of technological change in the West German chemical industry ; 1945 - 1961 - Stokes, Raymond G. 1956- (Cambridge Univ. Press, 1994)
Using approaches drawn from the history of technology, business history, and political and economic history, and taking advantage of material from a broad range of public and private archives, this study argues that it is impossible to explain the technological developments in the chemical industry from the end of the war until 1961 without exploring a number of other areas, including corresponding changes in the West German and worldwide political economies during the same period, as well as German traditions regarding technological change. Neither the move to petroleum-based feedstocks nor the pace of the transition was inevitable; rather, both depended on choices made by politicians and industrialists within the context of the political economy of the 1950s, as well as the context of prior German experience